Management of Medical Waste at the Takalar Regency Regional General Hospital, Makassar City - Musiana, Musiana; Syahruddin, Nursita; Djafar, Monisa A Hi; Jamila, Fidatul; Soamole, Maya Sari; Malaha, Naomi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Wastewater originating from hospitals is a very potential source of water pollution. This is because hospital wastewater contains quite high levels of organic compounds, contains dangerous chemical compounds and contains pathogenic microorganisms that can cause disease. The aim of the research is to find out how medical waste is managed including: how to store, collect, collect, transport, manage and final storage which is carried out at the regional general hospital in Takalar, Makassar City. The research method used is a descriptive survey research type, namely to find out how medical waste is managed in the regional general hospital in Takalar, Makassar City. This research was conducted at a hospital to look at the medical waste management system. Room selection is based on rooms that produce a lot of medical waste from hospital services.